High-Quality Materials - Khairul Fikri, Tamrin; Charles Bong, Hin Joo (Trans Tech Publications, 2021)
The book is collected from papers that were submitted by researchers from Universiti Malaysia Sarawak and their international collaborators addressing key results in the area of materials science and technologies of materials synthesis. We believe that the collected articles will be interesting and useful for many specialists in the areas of materials science, and materials processing technologies.